Impact of inserted long rest periods during repeated sprint exercise on performance adaptation - Ikutomo, A.; Kasai, N.; Goto, K. (European Journal of Sport Science, 2018)
Repeated sprint training consists of a series of brief maximal sprints, 3-7 s in duration, separated by short rest periods of <60 s. However, little is known about the influence of different rest period lengths between sprints on performance adaptation. We determined the influence of inserting long rest periods during repeated sprint training on performance adaptation in competitive athletes. Twenty-one well-trained athletes were separated into either the short rest period group (SHORT; n = 10) or the long rest period group (LONG; n = 11). The training protocol for both groups consisted of two sets of 12 x 6-s maximal cycle sprints with 24 s of rest between sprints. However, in the LONG group, an active rest period of 7 min was inserted every three sprints to attenuate the power output decrement during the latter half of the sprints. The training was performed 3 d/week for 3 weeks. Before and after the training period, repeated sprint ability [12 × 6-s maximal sprint (pedaling) with 24-s rest] was evaluated. Maximal power output during the repeated sprint test was significantly increased only in the LONG group (P < .05). Both groups showed a similar increase in power output during the latter half of sprints (P < .05). The LONG group showed a significant increase in (P < .05). These results suggest that repeated sprint training with insertion of longer rest periods is an efficient strategy for improving maximal power output compared with the same training separated by short rest periods alone.